In Situ Solidified Gel Polymer Electrolytes for Stable Solid−State Lithium Batteries at High Temperatures - Junfeng Ma; Zhiyan Wang; Jinghua Wu; Zhi Gu; Xing Xin; Xiayin Yao (Batteries, 2022)
Lithium metal batteries have attracted much attention due to their high energy density. However, the critical safety issues and chemical instability of conventional liquid electrolytes in lithium metal batteries significantly limit their practical application. Herein, we propose polyethylene (PE)−based gel polymer electrolytes by in situ polymerization, which comprise a PE skeleton, polyethylene glycol and lithium bis(trifluoromethylsulfonyl)imide as well as liquid carbonate electrolytes. The obtained PE−based gel polymer electrolyte exhibits good interfacial compatibility with electrodes, high ion conductivity, and wide electrochemical window at high temperatures. Moreover, the assembled LiFePO4//Li solid−state batteries employing PE−based gel polymer electrolyte with 50% liquid carbonate electrolytes deliver good rate performance and excellent cyclic life at both 60 °C and 80 °C. In particular, they achieve high specific capacities of 158.5 mA h g−1 with a retention of 98.87% after 100 cycles under 80 °C at 0.5 C. The in situ solidified method for preparing PE−based gel polymer electrolytes proposes a feasible approach for the practical application of lithium metal batteries.